PENGARUH POLA ASUH GENERASI X DAN GENERASI Y (MILENIAL) TERHADAP KARAKTER ANAK USIA DINI - Sulistiatun Hafifah; RR. Deni Widjayatri (STPI Bina Insan Mulia Yogyakarta, 2022)
Child development is very dependent on parenting, character, personality and other aspects of development will develop along with parenting carried out by parents. Old people were born in their respective generations, starting from the Baby Boomers generation, Generation X, Generation Y or Millennials, Generation Z and subsequent generations. Each generation level has different characteristics and ways of educating children with different backgrounds. For this reason, this study aims to describe the effect of parenting of Generation X and Generation Y (Millennials) in educating early childhood. This study uses a literature study method by analyzing articles published from 2018-2021 fulltext. The data was obtained from the Journal of Early Childhood Education and ResearchGate, and Google Scholar. The keywords used are Parenting Parenting, Generation X and Generation Z (Millennials), and Early Childhood. The results of the literature study research on the effect of parenting styles x and y (millennials) on the character of early childhood is that parenting carried out by parents in Generations X and Y (Millennials) is proven to have a positive influence. A healthy and positive parenting pattern will grow the child's character to become a better person.